The Adventure of Reading: Literature and Philosophy, Cavell and Beauvoir - Moi, Toril (Literature and theology, 2011)
Is there a way of reading philosophically without imposing a pre-existing philosophy on the literary text? Turning first to the work of Stanley Cavell, then to Simone de Beauvoir's often neglected accounts of reading, this essay shows that such a philosophical reading can be understood as a form of aesthetic experience in which the reader lets the work teach her how to read it. The reader must be willing to let her own experience (of philosophy, of life) be educated by the work. A similar view can be found in Cora Diamond's (and Beauvoir's) suggestion that the reader must be open to the adventure proposed by the text.